Activation Energy, Temperature Coefficient and Q10 Value Estimations of the Growth of Rhodotorula sp. Strain MBH23 on Acrylamide (Journal of Environmental Microbiology and Toxicology, 2024)
model being one of the most commonly used due to its simplicity and requiring only a few parameters. Temperature is a key factor that impacts microbial growth and their metabolic activities on various substrates. Because of their small size, microorgan-isms are very sensitive to the changes in environmental temperatures. The growth behavior of Rhodotorula sp. strain MBH23 on acrylamide reveals a unique chevron-like pattern in apparent activation energy, with a notable breakpoint at 28.05°C. The analysis revealed two distinct ranges for activation energy: 32–40°C with a value of 60.66 kJ/mol and 20–27°C with 51.60 kJ/mol. Within the 32–40°C range, the Q₁₀ value, which measures the rate of reac-tion change with temperature, was found to be 2.15, while the theta value, indicating the temperature coefficient, was 1.08. These findings offer important insights into how acryla-mide breaks down and moves, particularly in the context of bioremediation efforts. Study provides valuable insights for predicting acrylamide degradation and its movement during bioremediation processes.
Keywords: Acrylamide-degrading; Rhodotorula sp. Strain MBH23; Temperature; Arrhenius plot; Breakpoint